PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PRODUKSI JAGUNG DI DESA NGARU-NGARU KABUPATEN BOYOLALI - SRI WIJIASTUTI (MANAJEMEN DAN KEUANGAN, 2011)
The study about the influence of production factors to cron product at Ngaru-Ngaru village, Boyolali Regency purpose to know : I) the discriplive cost of seed, fertilizer, water, planting, hoeing to corn product. 2) how far the influence of seed fertilizer, water, planting, hoeing to corn product. 3) the scale of the decrease or increase of corn product. The study is done by using survey method and the sample by proportional random sampling, took 30 farmers to he respondents. Method used to know how far the influence of:;eed fertilizer, water, corn product. To know the scale of the decrease or increase corn product used the pettern of: bi I decrease, bi : 1 increase. The result of the analysis show that the regression coefficient of Bj is 0,896 means seed variable has positive influence. B-j is -0,286 means TS fertilizer variable has negative influence. B^ is -0,164 means 7.A fertilizer variable has negative influence, Bj is 2,344 means Urea fertilizer variable has positive influence, li 5 is 3.426 means animal waste manure variable has positive influence. B(, is -1,046 means tractor cost variable has negative influence, By is 0,541 means water cost variable has positive influence. B^ is -0.636 means planting variable has negative influence, B9 is -2,364 means hoeing variable has negative influence.